How Are We Doing? A Brief Guide to the Evaluation of School-Business Partnerships. - Massachusetts State Dept. of Education, Quincy. Office of Community Education; Massachusetts State Dept. of Education, Quincy. Office of Community Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
This pamphlet suggests what to evaluate in a school-business partnership, how to evaluate it, and how to determine whether a partnership has made a difference. The section called "Why Evaluate?" lists six questions to which evaluation frequently yields the answers. The next section explains the purpose of four steps in preparing to evaluate (review the mission and goals of the partnership and the objectives of the project, determine the purposes to which the evaluative information will be put, identify measures of achievement that can be correlated with each goal, and develop an evaluation plan) and also speaks briefly of a more formal, quantitative approach to evaluation. The next section lists 20 items that have been part of formal and informal partnership evaluations and also suggests six less quantifiable factors that can be assessed. A section on evaluation methods suggests four activities (regular meetings at which partnership programs are reviewed and redirected as necessary, surveys with the various constituencies in the partnership, interviews with those same constituencies, and direct observations of the effectiveness of programs). Third-party, or external, evaluations are also mentioned. The section on reports to the partners discusses with whom the evaluation information should be shared. Three descriptions of program evaluations appear in the section called "Evaluation at Work." The pamphlet concludes with a list of nine resources. (CML)
Availability: Office of Community Education, Massachusetts Dept. of Education, 1385 Hancock Street, Quincy, MA 02169.
ERIC Note: Developed by the Extended Committee for Industry-Education Partnerships.
Practitioners.
Community.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Accountability; Cooperative Programs; Elementary Secondary Education; Program Effectiveness; Program Evaluation; School Business Relationship; School Community Programs; School Community Relationship; Self Evaluation (Groups); Guides, Non-Classroom.